Making history : Josephus and historical method - Rodgers, Zuleika. (Supplements to the Journal for the study of Judaism, 2007)
The encounter between interpretation and history in the writings of Josephus provides the conceptual framework for this collection of essays. The contributions in this volume, which were presented at an international colloquium entitled "Josephus: Interpretation and History" held in Dublin in 2004, are united, not by a single view of Josephus, but by the question of historical method, both ancient and modern. These essays take up aspects of a problem basic to all researchers who would use Josephus for historical purposes, namely: What is the relationship between narratives and history? Organized thematically, the volume reflects a critical engagement with the texts of Josephus, other literary texts, case studies of particular events, and material remains.